Linkage analysis in Usher syndrome type I (USH1) families from Spain. - Espinós, C (1998)
Usher syndrome (USH) is an autosomal recessive hereditary disorder characterised by congenital sensorineural hearing loss and gradual visual impairment secondary to retinitis pigmentosa (RP). The disorder is clinically and genetically heterogeneous. With regard to Usher type I (USH1), several subtypes have been described, the most frequent being USH1B located on chromosome 11q13.5. Of 18 USH1 families studied by linkage analysis, 12 (67%) showed significant lod score values for locus D11S527 (Zmax=14.032, theta=0.000) situated on chromosome 11q. Our findings suggest considerable genetic heterogeneity in the Spanish USH1 population. It is important to note that one of our families linked to the USH1B locus shows interesting intrafamilial clinical variability. As regards the remaining six USH1 families, the linkage analysis did not provide conclusive data, although two of them show slight linkage to markers located on chromosome 3q (Zmax=1.880, theta=0.000 for D3S1279), the same location that had previously been assigned to some USH3 families.